Fractional Dynamics and Systems with Power-Law Memory - Edelman, M.; Machado, J.A. Tenreiro (Discontinuity, Nonlinearity, and Complexity, 2026)
The special issue of DNC “Fractional Dynamics and Systems with Power- Law Memory” contains papers related to presentations given at the 5th Conference on Nonlinear Science and Complexity, NSC’14, held on August 4-9, 2014 in Xi’an Jiaotong University, Xi’an, P. R. of China. Within this conference the authors proposed two mini-symposia: “Nonlinear Fractional Dynamics and Systems with Memory” and “Fractional Calculus Applications”.